Haematological and Demographic Study in Children Infected with Enterobiasis in Al Diwaniyah Province, Iraq - Dohan, Baraa Ali Mohammed; Al-Warid, Harith Saeed (Iraqi Journal of Science, 2022)
Enterobius vermicularis infection is considered as one of the important causes of anaemia and malnutrition among children. This topic has recently received an increased amount of attention. The objective of this study is to evaluate the demographical, anthropometrical, nutritional, and haematological status of E. vermicularis infection among children. This study was conducted in Al Diwaniyah province, south of Iraq, for the period of October 2020 to the end of January 2021. The study included 122 children from both genders (males, n= 61, and females, n=61) and their ages ranged between 1 and 14 years. Nutritional status, body mass index (BMI), BMI percentile, and weight- for- age Z score were evaluated for some participants. In addition, samples of cellophane tape and blood were collected from all participants. The cellophane tape samples were examined microscopically for E. vermicularis detection, whereas blood samples were processed to evaluate several parameters, which were hemoglobin, serum iron, and total iron binding capacity (TIBC), ferritin, and vitamin B12. The results revealed a high infection rate (73.77%) among the studied population. The results also showed a significant correlation between gender and the occurrence of E. vermicularis infection. Males showed a higher risk of enterobiasis than females. While no association was noticed between each of age, nutritional status, and enterobiasis. Also, a significant correlation was recorded between E. vermicularis positive status and anaemia. The results showed that each of BMI, weight- for- age Z score, haemoglobin, serum iron, total iron binding capacity (TIBC), and ferritin had significantly lower values among those who were positive for E. vermicularis. Finally, the level of vitamin B12 was insignificantly decreased in children with enteroniasis. These findings indicate that more hematological changes are expected to occur in children with enterobiasis. Therefore, further consideration and investigation would be required on this topic in Iraq.